Antidepressant dispensing before, during, and after pregnancy in New Zealand, 2005‒2014. (27th April 2021) - Donald, Sarah; Sharples, Katrina; Barson, Dave; Horsburgh, Simon; Parkin, Lianne
Abstract : Background: Depression during pregnancy is associated with a number of negative impacts on maternal and infant health, therefore good control of depression in pregnant women is crucial. There is a lack of population‐level information about patterns of antidepressant use during pregnancy in New Zealand. Aim: To describe antidepressant dispensing patterns before, during, and after pregnancy in New Zealand, 2005–2014. Materials and Methods: Antidepressant dispensing records from 270 days prior to pregnancy through to 360 days after pregnancy end were linked with 805 990 pregnancies in the New Zealand Pregnancy Cohort. Proportions (and 95% confidence intervals) with at least one dispensing were calculated for the periods before, during, and after pregnancy and compared over time and by maternal characteristics. Results: Dispensing during the first trimester was lower than in the pre‐pregnancy and post‐pregnancy periods, and dropped further in later trimesters. The proportion of pregnancies during which an antidepressant was dispensed rose from 3.1 to 4.9% over the study years. Around 80% of those with a dispensing received a selective serotonin reuptake inhibitor. Dispensing before, during, and after pregnancy varied by ethnicity, age, smoking status, and body mass index. Among women taking an antidepressant before pregnancy, younger women and those of Māori, Pacific, or Asian ethnicity were less likely to continue therapy during pregnancy. Conclusions: This study has established a baseline for antidepressant use around pregnancy in New Zealand, documented increasing use over time, and demonstrated that known ethnic differences in antidepressant use are also evident in the pregnant population.